Analysis of Zakat Distribution Accountability at BAZNAS Sukabumi City Based on the “Hadd Kifayah” Perspective - Khoirunisa; Sulaeman; Idang Nurodin (Muhasabatuna : Jurnal Akuntansi Syariah, 2026)
Zakat plays a strategic role in poverty alleviation, yet national zakat collection realization has only reached 5.6% of its potential. Strong administrative accountability does not necessarily reflect substantive effectiveness in improving mustahik welfare. This study aims to analyze the implementation of zakat distribution accountability at BAZNAS Kota Sukabumi, the welfare level of mustahik based on the Had Kifayah perspective, and the contribution of accountability to that welfare. The study employs a qualitative descriptive method with a case study design. Data were collected through in-depth interviews with six informants (two BAZNAS staff and four mustahik), observation, and documentation, then analyzed using Ellwood's (1993) four accountability dimensions and the seven Had Kifayah dimensions from Puskas BAZNAS (2024). The results show that zakat distribution accountability at BAZNAS Kota Sukabumi has been adequately implemented, marked by an unqualified (WTP) audit opinion for ten consecutive years, a seven-stage distribution SOP, and the integration of Had Kifayah into mustahik assessment. However, program and policy evaluation remains output-oriented rather than outcome-oriented. In terms of welfare, the housing and transportation dimensions were fulfilled for nearly all informants, while the food dimension showed the largest gap. Program accountability provided the most direct contribution to mustahik fulfillment of Had Kifayah. This study recommends the systematic development of an outcome evaluation system based on Had Kifayah.